2017
DOI: 10.1016/j.cmi.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

mcr-1 is borne by highly diverse Escherichia coli isolates since 2004 in food-producing animals in Europe

Abstract: MCR-1 was detected yearly in European food-producing animal since 2004 with a high diversity of pulsotypes supporting the dissemination of mcr-1 via plasmids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 11 publications
(13 reference statements)
1
37
0
1
Order By: Relevance
“…ExPEC strains in these clonal groups may be derived from DEC strains and may have evolved into ExPEC through the accumulation of virulence factors (Brzuszkiewicz et al, 2006). Some regional monitoring investigations showed that CC10 strains from clinical patients, birds, and swine were associated with ciprofloxacin resistance and carried various CTX-M-type genes and mcr-1 (mediated colistin resistance) (Oteo et al, 2009;Giufre et al, 2012;Ramos et al, 2013;EI et al, 2017). The widespread dissemination of CC10 E. coli across wide areas, plus multidrug resistance, may lead to a public emergence similar to the ST131 lineage infections.…”
Section: Discussionmentioning
confidence: 99%
“…ExPEC strains in these clonal groups may be derived from DEC strains and may have evolved into ExPEC through the accumulation of virulence factors (Brzuszkiewicz et al, 2006). Some regional monitoring investigations showed that CC10 strains from clinical patients, birds, and swine were associated with ciprofloxacin resistance and carried various CTX-M-type genes and mcr-1 (mediated colistin resistance) (Oteo et al, 2009;Giufre et al, 2012;Ramos et al, 2013;EI et al, 2017). The widespread dissemination of CC10 E. coli across wide areas, plus multidrug resistance, may lead to a public emergence similar to the ST131 lineage infections.…”
Section: Discussionmentioning
confidence: 99%
“…The mcr-1 -positive gut bacteria included Escherichia coli ( E. coli ) [21, 22], S. enterica [23, 24], K. pneumoniae [6, 25, 26], Enterobacter aerogenes ( E. aerogenes ) [27], Kluyvera ascorbata [28], Citrobacter freundii [29], and Citrobacter braakii [30]. Not only does the mcr-1 gene appear in diversified E. coli isolates with different sequence types [20, 31], but also it coexists with the NDM-1 [32, 33] and its variants, like NDM-5 [34, 35] and NDM-9 [36]. Additionally, ESBL can be coproduced with MCR-1 from a single plasmid or a same bacterial isolate [3739].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, MLST analysis from sequence reads identified the sequence types ST132, ST48, ST4419, ST522, and ST10 (Table 1). In particular, the ST10 has been widely identified in animal, food, human, and environmental samples and associated with the production of CTX-M-type ESBLs and, more recently, the MCR-1 enzyme, denoting great versatility of this lineage for adaptation to different hosts (3,(19)(20)(21)(22)(23). Furthermore, the presence of IncX4 plasmids carrying the mcr-1 gene in E. coli isolates CF1.2, CF131, and CF132 was confirmed, as previously reported in human and animal clinical samples collected in this region (3,19).…”
mentioning
confidence: 99%